2021
DOI: 10.1002/ajmg.b.32833
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DNA methylation persist over time in males with severe alcohol use disorder—A longitudinal follow‐up study

Abstract: Treatment strategies for alcohol use disorder (AUD) aim for abstinence or harm reduction. While deranged biochemical parameters reverse with alcohol abstinence, whether molecular changes at the epigenetic level reverse is not clearly understood.We investigated whether the reduction from high alcohol use reflects DNA methylation at the gene-specific and global level. In subjects seeking treatment for severe AUD, we assessed gene-specific (aldehyde dehydrogenase [ALDH2]/methylene tetrahydrofolate reductase [MTHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In the current study we found hypomethylation of ALDH2 gene in AUD with cirrhosis (3.8±0.8) compared to AUD without cirrhosis (5.1±1.9). In a previous study we had reported ALDH2 methylation in a set of controls (4.2±0.7) (Soundararajan et al, 2021). Thus, cirrhosis and HCC (which is often its sequel) both appear to be associated with hypomethylation while the noncirrhotic phenotype of AUD has a higher methylation level.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the current study we found hypomethylation of ALDH2 gene in AUD with cirrhosis (3.8±0.8) compared to AUD without cirrhosis (5.1±1.9). In a previous study we had reported ALDH2 methylation in a set of controls (4.2±0.7) (Soundararajan et al, 2021). Thus, cirrhosis and HCC (which is often its sequel) both appear to be associated with hypomethylation while the noncirrhotic phenotype of AUD has a higher methylation level.…”
Section: Discussionmentioning
confidence: 86%
“…Consumption of excessive amounts of alcohol is also known to influence global DNA methylation, though studies have shown inconsistent findings (Zhang and Gelernter, 2017). Our earlier work looking at global DNA methylation using LINE1 (Long-Interspersed Nuclear Elements-1) loci showed hypomethylation in patients with AUD compared to controls (Soundararajan et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…A longitudinal study by Soundararajan et al. on males with severe alcohol use disorder show that the changes in DNA methylation persist over time, even at remission period of 3 months [111]. A close‐up investigation of the NR3C1 gene methylation in relation to alcohol consumption, depression, and obesity in a Brazilian population shows that NR3C1 hypomethylation is associated with alcohol consumption and obesity, whereas its hypermethylation is related to depression [112].…”
Section: Future Applicationsmentioning
confidence: 99%
“…In this sense, a slight disparity of 0.1% in GMe levels between two groups - cases and controls - could represent a significant difference of over 28,000 cytosines that are methylated distinctly throughout the human genome (which contains more than 28 million CpG sites) ( Luo et al, 2014 ). However, up to now, only AUD studies using GMe proxy-based approaches were performed, observing both hypermethylation ( Bönsch et al, 2004 ; Kim et al, 2016 ) or hypomethylation in individuals with AUD compared to controls ( Soundararajan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%